Fleet Management Information System Design PT. Bagus Amelia Jaya Uses the User Method Web-Based Centered Design - Lubis, Bagus Rizki; Suendri, Suendri (Journal of Electrical Engineering and Computer (JEECOM), 2025)
This study discusses the design of a Fleet Management Information System at PT. Bagus Amelia Jaya using a User Centered Design (UCD) approach and developed as a web-based application with the Laravel framework. The company's main problems include manual recording, the lack of a structured fleet maintenance schedule, limited visibility of fleet and driver data, and minimal support for operational decision-making. The methodology used combines Research & Development (R&D) with the UCD cycle: understanding the context of use, determining user needs, generating design solutions, and conducting iterative evaluations through usability testing. The research results are a system design that provides fleet data modules, service schedules, operational expenses, role-based user management, and structured reporting. The UCD approach ensures the interface design is aligned with the company's workflow and reduces the learning curve for internal users. This research is expected to fill the gap in previous research that predominantly focuses on technical aspects without comprehensive user involvement.